The Representation of the Traditional Residential in Jambi Malay Islamic Culture - Putra, Budi Arlius; Darisma Putri, Opi Teci (Sosial Budaya, 2023)
This study examines the relationship between architecture, conservation and tourism in representing a cultural character. This study specifically assesses building regulations which are the product of the Government's collaborative strategy between tourism planning and cultural conservation. The study of research directives focuses on approaches to tourism planning and regulation in maintaining cultural representation. The study uses the Jambi case study, evaluates legally binding guidelines in maintaining traditional architecture and investigates how local values are resistant to vernacular identities. This study shows that in Jambi there is a transformation towards the commercialization of local cultural products as a potential tourist attraction and the effect of modernity.